Use of wild edible plants: A comparative analysis of seven plant species for potential food applications - Ehsan Ali; Muhammad Farooq Azhar (Food and Humanity, 2026)

Comparative analysis of cow and buffalo milk based probiotic yoghurt formulations, for physicochemical, sensory, and in vitro biological activities - Muhammad Azhar Iqbal; Mian Anjum Murtaza; Aysha Sameen; Iram Hafiz; Ashiq Hussain; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Fakhria A. Al-Joufi (Food and Humanity, 2026)

Draft nuclear and complete mitochondrial genome assemblies of the flare-horned markhor (Capra falconeri): genomic resources for conservation and phylogenetics - Javeria Wali; Muhammad Waqas; Azhar Hussain Shah; Inam Ullah; Asif Mir; Zunnan Huang; Amjad Ali (Mammalian Genome, 2026)

Closing the selection gap in passive retrofit optimization: a pathway-based framework for resident-informed selection in old residential buildings in cold-region China - Pengfei Gao; Muhammad Farihan Irfan Mohd. Nor; Mohd Khairul Azhar Mat Sulaiman (Energy and Buildings, 2026)

From biosynthesis to food market translation of pullulan: AI-assisted production, structure-property-function interplay, regulatory perspectives, and commercialization - Muhammad Wajid Ullah; Su Sun; Zainab Jamil; Omar Mohammad Atta; Lili Zhang; Maleeha Azhar; Hidayat Ullah; Faryal Taimour; Mazhar Ul-Islam; Sehrish Manan; Yimin Fan; Zhiguo Wang (Carbohydrate Polymers, 2026)

Spatiotemporal assessment of water quality around Western Australian central business district using satellite multispectral imaging - Muhammad Hassnain; Cameron Veal; Muhammad Rizwan Azhar (Journal of Water Process Engineering, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

A Novel hybrid kinetic–equilibrium model for predicting syngas composition in coal char gasification: Coupling thin reaction zone kinetic with Gibbs free energy minimization - Takdir Syarif; Thahirah Arief; Muhammad Ikhsan Taipabu; Karthickeyan Viswananthan; Wei Wu; Badril Azhar (Fuel, 2026)

Retraction notice to “Does communicable diseases (including COVID-19) may increase global poverty risk? A cloud on the horizon” [Environ. Res. 187 (2020) 109668] - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Xuan Vinh Vo; Khalid Zaman (Environmental Research, 2026)

Pressmud Alleviates Cadmium Stress in Wheat by Enhancing Soil Microbial Activity, Nutrient Uptake and Limiting Cd Accumulation - Basit Haider; Muhammad Imran; Fuad Ameen; Hadeeqa Arshad; Azhar Hussain; Ruijia Liu; Asif Naeem (Water, Air, & Soil Pollution, 2026)

Feature Selection and Data Decomposition-Driven Drought Forecasting: Designing Hybrid Deep Learning Models - Ayesha Parveen; Muhammad Azhar; Muhammad Gulistan; Mumtaz Ali; Aitazaz A. Farooque (Water Resources Management, 2026)

Year-round fruiting by Muntingia calabura helps sustain urban frugivorous birds across tropical cityscapes - Muhammad Syafiq Yahya; Nuur Farhani Zulkifli; Sharifah Nur Atikah; Ahmad Razi Norhisham; Ruzana Sanusi; Badrul Azhar (Ornithology Research, 2026)

Artificial intelligence based predictive simulation and decision-support framework for full scale wastewater treatment systems - Muhammad Hassnain; Cameron Veal; Sarada M.W. Lee; Muhammad Rizwan Azhar (Journal of Water Process Engineering, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Improving subseasonal Indian summer monsoon rainfall forecasts with U-Net calibration - Emile D. Esmaili; Andrew W. Robertson; Muhammad Azhar Ehsan; Bohar Singh; Aaron Kaplan; Avijit Dey; Susmitha Joseph (Climate Dynamics, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Prevalence of Vitamin D Deficiency in Ataxia-Telangiectasia: A Systematic Review and Single Arm Meta-Analysis - Muhammad Junaid Iqbal; Muteeba Azhar; Hammad Javaid; Amina Hassan; Ayesha Masood; Michele Menotta (The Cerebellum, 2026)

High-resolution HPLC-MS/MS profiling of group A and group B seed saponins in 711 diverse soybean germplasms - Adebabay Tazeb; Shengrui Zhang; Yanan Hou; Azhar Iqbal; Aimal Nawaz Khattak; Muhammad Ahsan; Emmanuel Kofi Sie; Jing Li; Bin Li; Junming Sun (Food Chemistry, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Micromorphological assessment of pollen and foliar epidermal traits in Solanaceae using SEM characterization - Mehral Azhar; Muhammad Zafar; Salman Majeed; Saleh AlNadhari; Sayyara Ibadullayeva; Muhammad Rizwan Khan; Khuzin Dinislam; Nigar Mursal; Amna Shahid; Enkelejda Kucaj (The Science of Nature, 2026)

Exploring the Role of Mitochondrial Sirtuin 3 Gene in Gastric Cancer Risk Based on SNP Analysis and LORD-Q Assay - Ishrat Mahjabeen; Muhammad Zahid Hussain; Maria Fazal-Ul Haq; Azhar Mehmood; Muhammad Shahbaz Haris; Shereen Ali Khan; Anum Chaudhry; Farzana Hakim; Ayesha Zulfiqar Abbasi; Mahmood Akhtar Kayani (Biochemical Genetics, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Integrated Mechanical–NDT Evaluation of Moisture- and Weathering-Induced Weakening in Granite, Marble, and Limestone Joints - Waqas Ahmed; Azhar Ali; Abdul Rahim Asif; M. E. Al-Atroush; Muhammad Yasir (Rock Mechanics and Rock Engineering, 2026)

Microplastic exposure reduces multi-trophic biomass yield in a freshwater integrated aquaculture system - Gökhan Tunçelli; Muhammad Hanif Azhar; Devrim Memiş; Nuray Erkan; Idil Can-Tuncelli; Özkan Özden; Eda Dagsuyu; İsmet Burcu Turkyilmaz Mutlu; Refiye Yanardag (Aquaculture International, 2026)
Freshwater integrated multi-trophic aquaculture (IMTA) systems are increasingly used to enhance nutrient utilization efficiency; however, their performance under microplastic (MP) exposure remains poorly characterized. This study evaluated the effects of water-borne and feed-borne polyethylene (PE) MP (10–20 µm) on biomass production and filtration performance in a three-compartment freshwater IMTA system comprising rainbow trout ( Oncorhynchus mykiss ), freshwater mussels (Unionidae), and duckweed ( Lemna minor ). Fluorescent spherical MPs were applied in four treatments ( n = 3 tanks per treatment): control (no MPs), feed-borne MPs (5 particles per 100 g feed), water-borne MPs (35 particles L⁻ 1 at fish-tank inflow), and combined exposure. The exposure phase lasted 45 days with 15-day sampling intervals, followed by a 45-day depuration phase. Fish growth responses differed modestly among treatments during exposure, with transient reductions observed in MP-exposed groups relative to the control at intermediate sampling points. Mussel filtration capacity showed limited variation among treatments, with no consistent treatment-specific suppression across time. Duckweed biomass accumulation was lower under combined exposure compared with the control, whereas variability was higher in MP treatments during early growth stages. An integrated multi-trophic performance index calculated from terminal measurements indicated moderate reductions in overall system productivity under combined exposure relative to the control. During depuration, growth trajectories across treatments converged. These results indicate that elevated microplastic exposure can influence biomass distribution and productivity within freshwater IMTA systems, particularly under combined exposure scenarios.

Quercetin as a promising HIS-C inhibitor and novel therapeutic against antibacterial drug-resistant Acinetobacter baumannii: in vitro and in silico insights - Mohammed Salleh M. Ardawi; Samar A. Badreddine; Muhammad Yasir; Safaa A. Turkistani; Ahmed Afandi; Abdulaziz A. Kimawi; Samah O. Noor; Adhari Alselmi; Salma Mohammed Alsayed; Mada S. Alharthi; Vivek Dhar Dwivedi; Pradeep Sharma; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plant-derived biostimulants: Emerging trends, breakthroughs and challenges in 2024 - Qurat Ul Ain Hyder; Abida Aziz; Muhammad Farooq Azhar; Muhammad Hasnain Haider; Nazim Hussain (Organic Agriculture, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

Unveiling the bee pollinators interaction with Muntingia calabura: implications for urban biodiversity conservation in tropical cityscapes - Muhammad Syafiq Yahya; Nuur Farhani Zulkifli; Sharifah Nur Atikah; Ruzana Sanusi; Badrul Azhar; Ahmad Razi Norhisham (Journal of Insect Conservation, 2026)

Anti-arthritic effect of Helicteres isora L. ethanolic extract via modulation of cytokines and oxidative stress in CFA-induced arthritic rats - Muhammad Muzammil Nazir; Azhar Rafique; Salma Sultana; Asma Ashraf (Inflammopharmacology, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Emerging contaminants and their influence on plants: An in-depth review - Sadia Aziz; Sania Zaib; Azhar Iqbal; Muhammad Asif Chuadhry; Shaheen Shahzad; Bikram Dhara; Athanasios Alexiou; Partha Biswas; Mohamed M. Abdel-Daim; Shabana Bibi (Environmental Toxicology and Pharmacology, 2026)

Surface self-reconstruction of metal oxychalcogenide cluster activating lattice oxygen to catalyze oxygen evolution - Bolin Zhao; Rana Muhammad Irfan; Azhar Mahmood; Shamraiz Hussain Talib; Chuhao Liu; Li Niu (Chemical Engineering Journal, 2026)

Alien floral homogenizes the traditional knowledge diversity of isolated ethnic communities - Nausheen Niaz; Shiekh Marifatul Haq; Aadil Abdullah Khoja; Muhammad Waheed; Muhammad Azhar Jameel; Manzer H. Siddiqui; Ivana Vitasović-Kosić; Rainer W. Bussmann (Biological Invasions, 2026)

Fluorescence Interface Engineering of PEDOT: PSS–HTL and BPhen–ETL Layers in Alq₃-Based OLEDs for Biomedical Applications - Ghazi Aman Nowsherwan; Hafiz Muhammad Khubaib; Muhammad Azhar; Saira Riaz; Shahzad Naseem (Journal of Fluorescence, 2025)

Integrated Chitosan-based coagulation and microbubble pre-treatment for improved microplastic fibre removal from water - Nimesha Thathsarani; Mohadeseh Najafi; Mehdi Khiadani; Muhammad Rizwan Azhar; Masoumeh Zargar (Science of The Total Environment, 2025)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Mechanical characterization and impact resistance of concrete incorporating recycled thin-walled hollow tubular GFRP sections - Muhammad Rizwan Riaz; Muhammad Moeed Azhar; Muhammad Fahad Ejaz; Rizwan Azam; Muhammad Faraz Javaid (Innovative Infrastructure Solutions, 2025)

Deciphering the role of non-covalent interactions in CO2 Capture: A DFT and COSMO-RS study of amino acid-based ionic liquids - Hira Karim; Sabahat Sardar; Suhan Prasantha Panditharatne; Asad Mumtaz; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Management, 2025)

Harnessing the power of amphoterically modified Chitosan coagulants for enhanced Polyester microplastic fibre removal from water - Nimesha Thathsarani; Mohadeseh Najafi; Mehdi Khiadani; Muhammad Rizwan Azhar; Masoumeh Zargar (Journal of Environmental Management, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Alien flora of the Kingdom of Saudi Arabia: taxonomic composition, phylogenetic patterns, and invasion status - Shiekh Marifatul Haq; Muhammad Waheed; Muhammad Azhar Jameel; Łukasz Walas; M. Nasir Khan; Manzer H. Siddiqui; Saud Alamri; Anas E. AbuYahya; Rainer W. Bussmann (Biological Invasions, 2025)

Characterization of ambient air quality and its relationship with respiratory morbidity in typical cities of Northwest China (NWC) - Shah Zaib; Jianjiang Lu; Gao Yan; Xiaowen Yin; Xiaoning Lei; Muhammad Zeeshaan Shahid; Azhar Siddique; Mariam A. Yousaf Al-Nesf (Air Quality, Atmosphere & Health, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

The nexus between global value chains and productivity gains of ASEAN countries - Zia Ur Rahman; Wajid Khan; Musarat Abbas; Fatima Gulzar; Muhammad Azhar Farooq (Environment, Development and Sustainability, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Soft sensing of biological oxygen demand in industrial wastewater using machine learning models - Muhammad Hassnain; Sarada M.W. Lee; Muhammad Rizwan Azhar (Journal of Water Process Engineering, 2025)

Ferroptosis: a novel pathway in the pathogenesis and treatment of endometriosis - Xunshu Cheng; Muhammad Azhar Memon; Waseem Ali; Yonggang Ma (Journal of Molecular Histology, 2025)

Integration of multivariate indices to correlate pollen morphology and evolutionary adaptations in halophytes - Moona Nazish; Asif Kamal; Muhammad Azhar Khan; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Fozia Bibi; Jawaher Alkahtani; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Influence of temperature and relative humidity on the combined efficacy of insecticides and diatomaceous earth for the control of Trogoderma granarium on rough rice - Muhammad Bukhari; Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2025)

A comprehensive review on the recovery of lithium from lithium-ion batteries and spodumene - Asad Ali; Sadia Afrin; Abdul Hannan Asif; Yasir Arafat; Muhammad Rizwan Azhar (Journal of Environmental Management, 2025)

Cinnamon bark oil application and modified atmosphere packaging alleviates chilling injury, ethylene production and maintains antioxidant system in persimmons - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Muhammad Rizwan Azhar; Eben Afrifa-Yamoah; Andrew Woodward (Food Chemistry, 2025)

Expression Profiling of Genome-Wide Identified and Characterized Trans-Isoprenyl Diphosphate Synthase Family in Catharanthus roseus (L.) G. Don Under Stress Conditions - Muhammad Huzafa; Amjad Hassan; Batool Bashir; Azhar Mehmood; Jawad Ahmed (Plant Molecular Biology Reporter, 2025)

Biostratigraphy, Microfacies, and Palaeoenvironmental Dynamics of the Early Eocene Dungan Formation, Pakistan: implications for the Carbonate Ramp Evolution and Larger Foraminiferal Extinction and Origination Event (LFEO) during Global Warming - Muhammad Azhar Farooq Swati; Muhammad Hanif (Carbonates and Evaporites, 2025)

N-AquaRAM: A Cost-Efficient Deep Learning Accelerator for Real-Time Aquaponic Monitoring - Ali Siddique; Muhammad Azhar Iqbal; Jingqi Sun; Xu Zhang; Mang I. Vai; Sunbal Siddique (Agricultural Research, 2025)
Aquaponics is an emerging area of agricultural sciences that combines aquaculture and hydroponics in a symbiotic way to increase crop production. Though it offers a lot of advantages over traditional techniques, including chemical-free and soil-less farming, its commercial application suffers from some problems such as the lack of experienced manpower. To operate a stable smart aquaponic system, it is critical to estimate the fish size properly. In this context, the use of dedicated hardware for real-time aquaponic monitoring can greatly resolve the issue of inexperienced handlers. In this article, we present a complete methodology to train a deep neural network to perform fish size estimation in real time. To achieve high accuracy, a novel implementation of swish function is presented. This novel version is far more hardware efficient than the original one, while being extremely accurate. Moreover, we present a deep learning accelerator that can classify 40 million fish samples in a second. The dedicated real-time system is about 1600 times faster than the one based on general-purpose computers. The proposed neuromorphic accelerator consumes about 2600 slice registers on a low-end model of Virtex 6 FPGA series.

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Investigation of geoenvironmental contamination and risks of municipal solid waste disposal sites in urban Khyber Pakhtunkhwa, Pakistan - Muhammad Ayaz Khan; Abdullah Khan; Zia ur Rahman; Azhar Rashid; Khalid Latif (Environmental Geochemistry and Health, 2025)

Negative influence of suboptimal quality of drinking water on avian coronavirus pathogenesis and immune response: A Controlled Study - Muhammad Farooq; Awais Ghaffar; Ahmed Ali; Ryan Rahimi; Muhammad Azhar; Ishara M. Isham; Heshanthi Herath-Mudiyanselage; Sufna M. Suhail; Mohamed Faizal Abdul-Careem (Veterinary Immunology and Immunopathology, 2025)

The environmental impacts via life cycle assessment of activated carbon produced by Fiddlewood and Jacaranda biomass - Muhammad Amin; Hamad Hussain Shah; Muhammad Usman; Muhammad Azhar Iqbal (Clean Technologies and Environmental Policy, 2025)

Dual colorimetric sensing of Hg(II) and Fe(III) using sulfanilamide-stabilized silver nanoparticles and evaluating their photodegradation and antibacterial properties - Maria Kanwal; Muhammad Sher; Azhar Abbas; Shoaib Akhtar; Abu Bakar Siddique; Muhammad Naeem ul Hasan; Nasir Assad; Hassan A. Alhazmi; Hatem M.A. Amin (Journal of Water Process Engineering, 2025)

Enhanced removal of microplastic fibres using aluminium and chitosan-based coagulants assisted with microbubble technology - Nimesha Thathsarani; Mehdi Khiadani; Muhammad Rizwan Azhar; Masoumeh Zargar (Journal of Environmental Chemical Engineering, 2025)

Unravelling the role of non-covalent interactions using imidazolium and amino acid based organic salts for efficient CO2 capture: experimental, DFT and COSMO-RS explorations - Hira Karim; Sabahat Sardar; Asad Mumtaz; Anila Tabassum; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Cecilia Devi Wilfred; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Chemical Engineering, 2025)

Carissa macrocarpa Extract Based Greenly Synthesized AuNPs: A Sustainable Approach for Lead Ion Detection, Azo Dye Degradation, and Antimicrobial Applications - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Mamoon Ur Rasheed; Abdul Karim; Muhammad Mustaqeem; Muhammad Fayyaz ur Rehman; Mohammad Mahtab Alam; Amirah S. Alahmari (Water, Air, & Soil Pollution, 2025)

Dynamics of bi-susceptibility patterns in Covid-19 outbreaks and associated abstain strategies - Waheed Ahmad; Muhammad Rafiq; Azhar Iqbal Kashif Butt; Momina Zainab; Naeed Ahmad (Modeling Earth Systems and Environment, 2025)

Genome-wide identification and characterization of light-responsive FAR1 gene family in finger millet (Eleusine coracana) under abiotic stress - Urooba Abid; Azhar Iqbal; Mahnoor Mazher; Shabana Bibi; Sara Ashraf; Mohamed Kamel; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Muhammad Sajid (Genetic Resources and Crop Evolution, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Energy bandgap tuning of Sr-doped ZnO nanoparticles for photodegradation of azo dyes and antibacterial applications - Hufsa Ahmad; Abu Bakar Siddique; Saima Zaheer; Rabia Sattar; Azhar Abbas; Muhammad Amin; Rashad Al-Salahi; Hatem A. Abuelizz; M. Zubair Saleem (Journal of Water Process Engineering, 2025)

Effectiveness of pirimiphos-methyl, alpha-cypermethrin, spinetoram and thiamethoxam alone and in combination with diatomaceous earth for the control of Trogoderma granarium on rough rice - Muhammad Bukhari; Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2025)

A parametric study of particle size influence on sewage sludge-derived hydrochar and coal char co-gasification: Reactivity and carbon conversion analysis - Azhar Ali Laghari; Asma Leghari; Akash Kumar; Lata Kumari; Muhammad Rizwan; Qurat-ul-ain Abro; Memon Kashif Ali; Yongheng Shen; Qingxia Guo (Biomass and Bioenergy, 2025)

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Impacts of climate change on Pakistan’s weather patterns: a comprehensive study of temperature and precipitation trends - Hafiza Nida; Muhammad Kashif; Azhar Ali Janjua; Muhammad Aslam; Kamil Shahzad Cheema; Sami Ullah (Environmental Monitoring and Assessment, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Husnu Aktaş; Muhammad Azhar Nadeem; Yusuf Tutuş; Serap Doğan; Mehmet Karaman; İrfan Erdemci; Meng-Lu Wang; Jin-Ying Gou; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Molecular diversity and phylogenetic analysis of ten sheep breeds from Khyber Pakhtunkhwa, Pakistan, based on mitochondrial D-loop sequences - Shabir Ahmed; Muhammad Shahid Nadeem; Anna M. Johansson; Elisabeth Jonas; Khushi Muhammad; Sardar Azhar Mehmood (Mammalian Genome, 2025)

Increasing Salinity and Cadmium Enhanced Leaf Membrane Damage and H2O2 Production Irrespective of Reduced Sodium and Cadmium Accumulation in Wheat (Triticum aestivum L.) - Sajid Masood; Muhammad Ashraf; Mubshar Hussain; M. Farooq Azhar; M. Zafar-ul-Hye; Omer Farooq; Muhammad Aon; M. Tariq Javed (Journal of Soil Science and Plant Nutrition, 2025)

Continuous forests and non-IBA forest patches provide a safe haven for the tropical bird community in highly fragmented urban landscapes - Sharifah Nur Atikah; Muhammad Syafiq Yahya; Kang Woei Ong; Ruzana Sanusi; Ahmad Razi Norhisham; Badrul Azhar (Biodiversity and Conservation, 2025)

Food security in Punjab, Pakistan: rural views on climate disasters and their impacts - Muhammad Usman; Asghar Ali; Sajjad Ahmad Baig; Magdalena Radulescu; Azhar Abbas; Rimsha Akram (Environment, Development and Sustainability, 2025)

Grass fields play a greater role in maintaining avian biodiversity in urban landscapes than roadsides - H. M. Bichi; Badrul Azhar; Muhammad Syafiq Yahya; Muhamad Amir Hadi; A. A. Ogunjinmi; Norizah Kamarudin; Ahmad R. Norhisham (Urban Ecosystems, 2025)

Pyocins and Beyond: Exploring the World of Bacteriocins in Pseudomonas aeruginosa - Muhammad Suleman; Allah Rakha Yaseen; Shahbaz Ahmed; Zoha Khan; Asma Irshad; Afsah Pervaiz; Hafiza Hiba Rahman; Muteeba Azhar (Probiotics and Antimicrobial Proteins, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Detection of extended-spectrum beta-lactamase genes among Escherichia coli isolates of buffalo mastitis milk - Sarang Mazhar Abro; Jam Kashif Sahito; Abdul Ahad Soomro; Amjad Hussain Mirani; Muhammad Azhar Memon; Nazeer Hussain Kalhoro (Ecological Genetics and Genomics, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Kamil Tohiran; Dzulhelmi Muhammad Nasir; Maisarah Burhanuddin; Frisco Nobilly; Raja Zulkifli; Ramle Moslim; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (BioControl, 2024)

Corrigendum to “Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data” [Urban For. Urban Green. 98 (2024) 128415] - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Resilience underground: Understanding earthworm biomass responses to land use changes in the tropics - Badrul Azhar; Peter van der Meer; Rutger F. Sterenborg; Muhammad Syafiq Yahya; Norhisham Razi; Maisarah Burhanuddin; Jasmijn Rookmaker; Nur Syarihah Sahimi; Welmoed van der Pal; Frisco Nobilly; Siti Aisyah Mohd Azam; Meriam Ubachs; et al. (Biological Conservation, 2024)

In silico genome-wide analysis of the growth-regulating factor gene family and their expression profiling in Vitis vinifera under biotic stress - Nimra Nazir; Azhar Iqbal; Hadia Hussain; Faisal Ali; Khalid S. Almaary; Most. Nazmin Aktar; Muhammad Sajid; Mohammed Bourhia; Ahmad Mohammad Salamatullah (Cell Biochemistry and Biophysics, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.

Integrative approach to mitigate chromium toxicity in soil and enhance antioxidant activities in rice (Oryza sativa L.) using magnesium–iron nanocomposite and Staphylococcus aureus strains - Muhammad Azhar Ali; Muhammad Fahad Sardar; Afzal Ahmed Dar; Mohsin Niaz; Jawad Ali; Qian Wang; Yu Zheng; Yadan Luo; Gadah Albasher; Fengmin Li (Environmental Geochemistry and Health, 2024)

Pomegranate Peel Extract as 6-Phosphogluconate Dehydrogenase (6PGD) Inhibitor for Treatment of Breast Cancer - Saba Riaz; Azhar Rasul; Matloob Ahmad; Muhammad Asrar; Mudassir Hassan (Cell Biochemistry and Biophysics, 2024)

Control efficacy of isolates of Aspergillus nidulans and Aspergillus fumigatus against three destructive insect pests of stored grain - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal; Waheed Anwar; Muhammad Ali (Journal of Stored Products Research, 2024)

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

Correction: Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Maleated Hydroxyethyl Cellulose for the Efficient Removal of Cd(II) Ions from an Aqueous Solution: Isothermal, Kinetic and Regeneration Studies - Fatima Khan; Abu Bakar Siddique; Muhammad Imran Irfan; Muhammad Naeem ul Hassan; Muhammad Sher; Hassan A. Alhazmi; Abdulrahman N. Qramish; Hatem M. A. Amin; Rahman Qadir; Azhar Abbas (Water, Air, & Soil Pollution, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Site occupancy of native terrestrial mammals in oil palm landscapes is driven by the synergy of land sparing and sharing strategies - Satya Narayana; Amir Affandi; Muhammad Syafiq Yahya; Kamil Azmi Tohiran; Asrulsani Jambari; Ahmad Razi Norhisham; Badrul Azhar (Journal for Nature Conservation, 2024)

Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain; Azhar Siddique; Mujtaba Hassan; Kashif Rasool; Asif Shahzad; Syed Ali Asad Naqvi; Muhammad Raza Ul Mustafa (Environmental Research, 2024)

Recent Progress of Fluorescent Carbon Dots and Graphene Quantum Dots for Biosensors: Synthesis of Solution Methods and their Medical Applications - Rafaqat Khan; Amina Qureshi; Muhammad Azhar; Zia Ul Hassan; Sagheer Gul; Saeed Ahmad (Journal of Fluorescence, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Multi enzyme production from mixed untreated agricultural residues applied in enzymatic saccharification of lignocellulosic biomass for biofuel - Azhar Ali Tunio; Muhammad Naqvi; Abdul Sattar Qureshi; Imrana Khushk; Abdul Nabi Jatt; Abdul-Sattar Nizami; Habib Ahmed Naqvi; Tanzeel Rehman Charan; Miher Ali Bhutto; Nazir Ahmed Tunio; Qamer-u-Nisa (Process Safety and Environmental Protection, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Characterisation of the protein quality and composition of water kefir-fermented casein - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Stan Kubow; Ali Madi Almajwal; Sofyan Maghaydah; Ammar A. Razzak Mahmood; Ali Al-Qaisi; Haya AlFandi (Food Chemistry, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Repurposing FDA approved drugs against monkeypox virus DNA dependent RNA polymerase: virtual screening, normal mode analysis and molecular dynamics simulation studies - Ahmad Abdul Salam Khan; Muhammad Abrar Yousaf; Jahanzaib Azhar; Muhammad Faisal Maqbool; Ruqia Bibi (VirusDisease, 2024)

Elucidating the genetic diversity and population structure of international cotton germplasm using inter-primer binding site (iPBS) retrotransposon marker system - Binnur Yeşil Bayrıl; Allah Bakhsh; Muhammad Azhar Nadeem; Ufuk Demirel (Genetic Resources and Crop Evolution, 2024)

Tourism triumphs: unraveling the essence of Asia’s allure through governance, FDI, and natural bounties - Muhammad Zaheer Akhtar; Khalid Zaman; Muhammad Azhar Khan (Journal of Environmental Studies and Sciences, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Non-lamellar lyotropic liquid crystalline nanoparticles as nanocarriers for enhanced drug encapsulation of atorvastatin calcium and proanthocyanidins - Mardhiah Maslizan; Muhammad Salahuddin Haris; Mokrish Ajat; Siti Nurul Ain Md Jamil; Shah Christirani Azhar; N. Idayu Zahid; Intan Diana Mat Azmi (Chemistry and Physics of Lipids, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Calibrated probabilistic sub-seasonal forecasting for Pakistan’s monsoon rainfall in 2022 - Bohar Singh; Muhammad Azhar Ehsan; Andrew W. Robertson (Climate Dynamics, 2024)

Elucidating the Mechanism of Copper-Induced Photoluminescence Quenching in 2-Phenylbenzimidazole-5-Sulfonic Acid - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Poshmal Sumreen; Mamoona Tabassum; Shoaib Ashiq; Sheikh Aadil Abbas; Raheel Akram; Azhar Iqbal (Journal of Fluorescence, 2024)

Artificial intelligence models for validating and predicting the impact of chemical priming of hydrogen peroxide (H2O2) and light emitting diodes on in vitro grown industrial hemp (Cannabis sativa L.) - Muhammad Aasim; Buşra Yıldırım; Ahmet Say; Seyid Amjad Ali; Selim Aytaç; Muhammad Azhar Nadeem (Plant Molecular Biology, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Remediation of organic pollutant from the aqueous environment using in-house fabricated polyaniline-based hybrid composite (PANI-MnPBA/NiCoMnS) materials - Naseem Ahmad Khan; Muhammad Imran; Muhammad Nadeem Akhtar; Shabbir Hussain; Muhammad Azhar Khan; Ashwag Shami; Hafiz Iqbal (Chemosphere, 2024)

An experimental study on early age compression and shear strength properties of mixed clay soil - Azhar Abbas; Muhammad Akbar; Pan Huali; Ali Zar; Samar Ramzan; Zahoor Hussain (Arabian Journal of Geosciences, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Synergistic effect of CuO and Sr doped g-C3N4 for CO2 photoreduction into hydrocarbon fuels - Adil Raza; Azhar Ali Haidry; Zhengjun Yao; Muhammad Farooq Saleem; Asma A. Alothman; Saikh Mohammad (Chemical Engineering Journal, 2024)

Genome-wide association studies revealed DArTseq loci associated with agronomic traits in Turkish faba bean germplasm - Tolga Karaköy; Faruk Toklu; Eylem Tuğay Karagöl; Damla Uncuer; Yeter Çilesiz; Amjad Ali; Muhammad Azhar Nadeem; Hakan Özkan (Genetic Resources and Crop Evolution, 2024)

Antioxidant, anti-inflammatory, and anti-apoptotic effects of genkwanin against aflatoxin B1-induced testicular toxicity - Muhammad Umar Ijaz; Ayesha Ishtiaq; Arfa Tahir; Mughees Aizaz Alvi; Azhar Rafique; Peng Wang; Guo-ping Zhu (Toxicology and Applied Pharmacology, 2023)

Characterizing the HMA gene family in dragon fruit (Selenicereus undatus L.) and revealing their response to multifactorial stress combinations and melatonin-mediated tolerance - Qamar U Zaman; Latif Ullah Khan; Muhammad Azhar Hussain; Asif Ali; Liu Hui; Aamir Ali Khokhar; Darya Khan; Hua-Feng Wang (South African Journal of Botany, 2023)

Forecast skill of Bangladesh summer monsoon rainfall in C3S and NMME models after calibration - Muhammad Azhar Ehsan; Bohar Singh (Dynamics of Atmospheres and Oceans, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal Sajjad; Kashif Rasool; Azhar Siddique; Khadeeja Abdul Jabbar; Shimaa S. El-Malaha; Muhammad Umar Sohail; Fares Almomani; M. Rami Alfarra (Environmental Pollution, 2023)

Probing the Förster Resonance Energy Transfer Dynamics in Colloidal Donor-Acceptor Quantum Dots Assemblies - Muhammad Adnan Khalid; Muhammad Mubeen; Maria Mukhtar; Zumaira Siddique; Poshmal Sumreen; Firdevs Aydın; Demet Asil; Azhar Iqbal (Journal of Fluorescence, 2023)

Fluorescence Spectroscopy for the Assessment of Microbial Load in UVC Treated Water - Sana Imtiaz; Shahzad Anwar; Laiq Zada; Hina Ali; M. Saeed Khurram; Azhar Saeed; Muhammad Saleem (Journal of Fluorescence, 2023)

Therapeutic Potential of Selenium Nanoparticles on Letrozole-Induced Polycystic Ovarian Syndrome in Female Wistar Rats - Maisra Azhar Butt; Hafiz Muhammad Shafique; Mahjabeen Mustafa; Nurain Baig Moghul; Anum Munir; Urwah Shamas; Sobia Tabassum; Mubin Mustafa Kiyani (Biological Trace Element Research, 2023)

Efficacy of zinc-based nanoparticles in alleviating the abiotic stress in plants: current knowledge and future perspectives - Ali Raza Khan; Wardah Azhar; Xingming Fan; Zaid Ulhassan; Abdul Salam; Muhammad Ashraf; Yihua Liu; Yinbo Gan (Environmental Science and Pollution Research, 2023)

Overview of fermentation process: structure-function relationship on protein quality and non-nutritive compounds of plant-based proteins and carbohydrates - Mohammad Alrosan; Thuan-Chew Tan; Wee Yin Koh; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu’datt (Critical Reviews in Food Science and Nutrition, 2023)

Conservation planning in national parks may benefit from site occupancy and detection estimates of native animal species - Asrulsani Jambari; Tetsuro Hosaka; Miyabi Nakabayashi; Muhammad Syafiq Yahya; Badrul Azhar (Journal for Nature Conservation, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Natural occurrence of fungal species on the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae), in Punjab, Pakistan - Tiyyabah Khan; Hafiz Azhar Ali Khan; Waheed Anwar; Muhammad Rizwan Khan; Muhammad Umer (International Journal of Tropical Insect Science, 2023)

Seed priming with nano-silica effectively ameliorates chromium toxicity in Brassica napus - Zaid Ulhassan; Su Yang; Di He; Ali Raza Khan; Abdul Salam; Wardah Azhar; Sajid Muhammad; Skhawat Ali; Yasir Hamid; Imran Khan; Mohamed Salah Sheteiwy; Weijun Zhou (Journal of Hazardous Materials, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

Identifying indicator bird species for sustainable oil palm plantation certification - Zulkifli Nursyamin; Muhammad Syafiq Yahya; Sharifah Nur Atikah; Kamil Azmi Tohiran; Ahmad R. Norhisham; Nurul Wahida Othman; Alex M. Lechner; Badrul Azhar (Journal of Cleaner Production, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Multi-species rotational grazing of small ruminants regenerates undergrowth vegetation while controlling weeds in the oil palm silvopastoral system - Kamil Azmi Tohiran; Frisco Nobilly; Raja Zulkifli; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Md Zainal Rasyidi; Badrul Azhar (Agricultural Systems, 2023)

Do silvopastoral management practices affect biological pest control in oil palm plantations? - Frisco Nobilly; Sharifah Nur Atikah; Muhammad Syafiq Yahya; Shokri Jusoh; Thomas M. R. Maxwell; Ahmad Razi Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Badrul Azhar (BioControl, 2023)

Increased health risk assessment in different vegetables grown under untreated sewerage irrigation regime due to higher heavy metals accumulation - Zeshan Hassan; Ammara Hassan; Muhaiman Riaz; Azhar Abbas Khan; Sami Ul-Allah; Umbreen Shehzad; Muhammad Khurshid; Ali Bakhsh; Jawad Munawar Shah; Zahid Manzoor (Environmental Science and Pollution Research, 2023)

Exogenous application of low and high molecular weight organic acids differentially affected the uptake of cadmium in wheat-rice cropping system in alkaline calcareous soil - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Muhammad Azhar; Muhammad Rizwan; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Zahoor Ahmad (Environmental Pollution, 2023)

Extraction of dietary fiber and polyphenols from mango peel and its therapeutic potential to improve gut health - Amna Tariq; Amna Sahar; Muhammad Usman; Aysha Sameen; Marriam Azhar; Rimsha Tahir; Rimsha Younas; Muhammad Issa Khan (Food Bioscience, 2023)

A systematic literature review on public participation in decision-making for local authority planning: A decade of progress and challenges - Azlan Abas; Kadir Arifin; Mohd Azhar Mohamed Ali; Muhammad Khairil (Environmental Development, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Elucidating the genetic variations among Turkish grape varieties using morphological and molecular markers - Ahmet Sümbül; Ercan Yildiz; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2023)

Potential of agroforestry orchards as a conservation set-aside initiative in industrial rubber tree and oil palm plantations for avian biodiversity - Muhammad Syafiq Yahya; Sharifah Nur Atikah; Izereen Mukri; Aslinda Oon; Ainil Hawa; Ruzana Sanusi; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (Biodiversity and Conservation, 2023)

Spinach-derived boron-doped g-C3N4/TiO2 composites for efficient photo-degradation of methylene blue dye - Sadia Faryad; Umair Azhar; Muhammad Bilal Tahir; Wahid Ali; Muhammad Arif; Muhammad Sagir (Chemosphere, 2023)

Synthesis and Characterizations of Graphene/Copper Ferrite for Efficient Arsenic Removal - M. Abdullah; G. Murtaza; Muhammad Azhar Khan (Water, Air, & Soil Pollution, 2023)

Understanding the quality and potential of groundwater for human purposes and peat fire disaster mitigation - Nur Islami; Mitri Irianti; Azhar Azhar; Muhammad Nor; Fakhruddin Fakhruddin (Arabian Journal of Geosciences, 2023)

Poultry manure gleaned antibiotic residues in soil environment: A perspective of spatial variability and influencing factors - Azhar Rashid; Juma Muhammad; Sardar Khan; Aatika Kanwal; Qian Sun (Chemosphere, 2023)

Evaluation of quality and protein structure of natural water kefir-fermented quinoa protein concentrates - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Ghada Mohamed Aleid; Mohammad N. Alhamad; Sofyan Maghaydah (Food Chemistry, 2023)

Agroforestry orchards support greater butterfly diversity than monoculture plantations in the tropics - Wan Mamat Wan Zaki; Muhammad Syafiq Yahya; Ahmad R. Norhisham; Ruzana Sanusi; Peter J. van der Meer; Badrul Azhar (Oecologia, 2023)

Modelling wellbeing of farmers by using nexus of climate change risk perception, adaptation strategies, and their drivers on irrigation water in Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Sajjad Ahmad Baig; Khalid Mushtaq; Azhar Abbas; Rimsha Akram; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Prediction and interpretation of antibiotic-resistance genes occurrence at recreational beaches using machine learning models - Sara Iftikhar; Asad Mustafa Karim; Aoun Murtaza Karim; Mujahid Aizaz Karim; Muhammad Aslam; Fazila Rubab; Sumera Kausar Malik; Jeong Eun Kwon; Imran Hussain; Esam I. Azhar; Se Chan Kang; Muhammad Yasir (Journal of Environmental Management, 2023)

Development of methods for the simplification of complex group built causal loop diagrams: A case study of the Rechna doab - Muhammad Asif; Azhar Inam; Jan Adamowski; Muhammad Shoaib; Hisham Tariq; Shakil Ahmad; Mohammad Reza Alizadeh; Aftab Nazeer (Ecological Modelling, 2023)

Bacillus Species as Direct-Fed Microbial Antibiotic Alternatives for Monogastric Production - Shifa A. Bahaddad; Meshal H. K. Almalki; Othman A. Alghamdi; Sayed S. Sohrab; Muhammad Yasir; Esam I. Azhar; Hichem Chouayekh (Probiotics and Antimicrobial Proteins, 2023)

Climate-induced optimal wheat cropping season and mapping districts vulnerabilities in Punjab, Pakistan - Azhar Ali Janjua; Muhammad Aslam (Environment, Development and Sustainability, 2023)

The Combined Effect of Beetroot Peel Extract, Chilling, and Vacuum Packaging on the Shelf-Life of Deccan Mahseer ( Tor khudree ) Steaks - Hafsa Maqbool; Zynudheen Abubacker; Muhammad P. Safeena; Mudassir Azhar; C.G. Joshy (Journal of Aquatic Food Product Technology, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Assessing the genetic diversity in hawthorn (Crataegus spp.) genotypes using morphological, phytochemical and molecular markers - Ercan Yildiz; Ahmet Sümbül; Mehmet Yaman; Muhammad Azhar Nadeem; Ahmet Say; Faheem Shehzad Baloch; Gheorghe Cristian Popescu (Genetic Resources and Crop Evolution, 2023)

The influence of compost amendments on bioaccumulation of potentially toxic elements by pea plant cultivated in mine degraded soils - Abdulnour Ali Jazem Ghanim; Muhammad Azhar Shah; Mehboob Alam; Anwarzeb Khan; Muhammad Amjad Khan; Saifur Rahman; Mabkhoot A. Alsaiari; Mohammed Jalalah; Mohammad Kamal Asif Khan; Muhammad Irfan; Zawar Hussain (Arabian Journal of Geosciences, 2023)

A walk of corporate sustainability towards sustainable development: a bibliometric analysis of literature from 2005 to 2021 - Ahmad Ali Jan; Fong-Woon Lai; Junaid Siddique; Muhammad Zahid; Syed Emad Azhar Ali (Environmental Science and Pollution Research, 2022)

Taxonomy and distribution of butterfly fauna of family pieridae (lepidoptera) in district abbottabad, Khyber Pakhtunkhwa, Pakistan - Sidra Taj; Shoaib Ali; Shabir Ahmed; Muhammad Ather Rafi; Sardar Azhar Mehmood; Muzafar Shah (International Journal of Tropical Insect Science, 2022)

Evaluation of Potential Predictability of Indian Summer Monsoon Rainfall in ECMWF's Fifth-Generation Seasonal Forecast System (SEAS5) - Raju Attada; Muhammad Azhar Ehsan; Prasanth A. Pillai (Pure and Applied Geophysics, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Dirty versus clean fuel for cooking in Pakistan: regional mapping and correlates - Tusawar Iftikhar Ahmad; Muhammad Atif Nawaz; Kokab Kiran; Vishal Dagar; Muhammad Azhar Bhatti; Altaf Hussain (Environmental Science and Pollution Research, 2022)

Biopesticides and insect pest management - Kanwal Hanif; Muhammad Zubair; Dilbar Hussain; Sikander Ali; Muhammad Saleem; Hafiz Azhar Ali Khan; Tamsila Nazir; Muhammad Waqas ul Hassan (International Journal of Tropical Insect Science, 2022)

Light-emitting diodes induced in vitro regeneration of Alternanthera reineckii mini and validation via machine learning algorithms - Muhammad Aasim; Seyid Amjad Ali; Pınar Bekiş; Muhammad Azhar Nadeem (In Vitro Cellular & Developmental Biology - Plant, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Recent progress in omics and biotechnological approaches for improved mango cultivars in Pakistan - Ghassan Zahid; Yıldız Aka Kaçar; Flavien Shimira; Sara Iftikhar; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Molecular forces governing protein-protein interaction: Structure-function relationship of complexes protein in the food industry - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt (Critical Reviews in Food Science and Nutrition, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Arabiibacter massiliensis gen. nov. sp. nov., New Anaerobic Bacterium Isolated from the Human Gut - Cheikh Ibrahima Lo; Sory Ibrahima Traore; Awa Diop; Melhem Bilen; Esam Ibraheem Azhar; Fehmida Bibi; Asif Jiman-Fatani; Muhammad Yasir; Jean-Christophe Lagier; Didier Raoult; Florence Fenollar; Pierre-Edouard Fournier (Current Microbiology, 2022)

Nonlinearity in the relationship between COVID-19 cases and carbon damages: controlling financial development, green energy, and R&D expenditures for shared prosperity - Muhammad Khalid Anser; Danish Iqbal Godil; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Hailan Salamun; Sasmoko; Yasinta Indrianti; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Chemical characterisation, in vitro antioxidant, cytotoxicity and safety evaluation of Polystichum braunii (Spenn.) fee roots - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Azhar Rasul; Mirza Muhammad Faran Ashraf Baig (Natural Product Research, 2021)

Anticonvulsant activity of methanolic extract of Withania cogulans in mice - Zenat Fatima Khattak; Bushra Ansari; Muhammad Jamal; Abdul Aleem Awan; Muhammad Azhar Sherkheli; Rizwan ul Haq (Metabolic Brain Disease, 2021)

The impact of coal combustion, nitrous oxide emissions, and traffic emissions on COVID-19 cases: a Markov-switching approach - Muhammad Khalid Anser; Danish Iqbal Godil; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

The mediating role of ICTs in the relationship between international tourism and environmental degradation: fit as a fiddle - Muhammad Khalid Anser; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Seasonal predictability of Ethiopian Kiremt rainfall and forecast skill of ECMWF's SEAS5 model - Muhammad Azhar Ehsan; Michael K. Tippett; Andrew W. Robertson; Mansour Almazroui; Muhammad Ismail; Tufa Dinku; Nachiketa Acharya; Asher Siebert; Jemal Seid Ahmed; Asaminew Teshome (Climate Dynamics, 2021)

Rainfall forecasting in upper Indus basin using various artificial intelligence techniques - Muhammad Hammad; Muhammad Shoaib; Hamza Salahudin; Muhammad Azhar Inam Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah (Stochastic Environmental Research and Risk Assessment, 2021)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

Financial development, oil resources, and environmental degradation in pandemic recession: to go down in flames - Muhammad Khalid Anser; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Does COVID-19 pandemic disrupt sustainable supply chain process? Covering some new global facts - Muhammad Khalid Anser; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Deciphering the genetic diversity and population structure of Turkish bread wheat germplasm using iPBS-retrotransposons markers - Muhammad Azhar Nadeem (Molecular Biology Reports, 2021)

Exploring the genetic diversity and population structure of scarlet eggplant germplasm from Rwanda through iPBS-retrotransposon markers - Flavien Shimira; Hatice Filiz Boyaci; Yeter Çilesiz; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Hatıra Taşkin (Molecular Biology Reports, 2021)

Clostridium culturomicium sp. nov. and Clostridium jeddahitimonense sp. nov., novel members of the Clostridium genus isolated from the stool of an obese Saudi Arabian - Hoang Thong Kieu; Noémie Garrigou; Amael Fadlane; Ludivine Brechard; Nicholas Armstrong; Philippe Decloquement; Muhammad Yasir; Esam Ibraheem Azhar; Saad B. Al-Masaudi; Jean-Christophe Lagier; Maryam Tidjani Alou; Didier Raoult (Current Microbiology, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Efficacy of rhizobacterial exopolysaccharides in improving plant growth, physiology, and soil properties - Abubakar Dar; Zahir Ahmad Zahir; Muhammad Iqbal; Atif Mehmood; Atif Javed; Azhar Hussain; Bushra; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2021)

Genetic dissection of days to flowering via genome-wide association studies in Turkish common bean germplasm - Muhammad Azhar Nadeem; Ephrem Habyarimana; Tolga Karaköy; Faheem Shehzad Baloch (Physiology and Molecular Biology of Plants, 2021)

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Saba Shahrum; Shanila Zahra; Saima Shabbir; Azhar Iqbal (Journal of Fluorescence, 2021)

Progress in nuclear energy with carbon pricing to achieve environmental sustainability agenda: on the edge of one’s seat - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Demographic, psychological, and environmental factors affecting student’s health during the COVID-19 pandemic: on the rocks - Muhammad Khalid Anser; Muhammad Sharif; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Genome-wide association and transcriptome analysis of root color-related genes in Gossypium arboreum L. - Zibo Zhao; Daowu Hu; Muhammad Tehseen Azhar; Hongge Li; Chenhui Ma; Shoupu He; Xiaoyang Wang; Gaofei Sun; Tahir Mahmood; Washu Dev; Xiongming Du (Planta, 2021)

The role of information and communication technologies in mitigating carbon emissions: evidence from panel quantile regression - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

Chemical characterization and anti-arthritic appraisal of Monotheca buxifolia methanolic extract in Complete Freund’s Adjuvant-induced arthritis in Wistar rats - Muhammad Furqan Akhtar; Khushdil Khan; Ammara Saleem; Mirza Muhammad Faran Ashraf Baig; Azhar Rasul; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Disintegration of uncertainties associated with real-time multi-satellite precipitation products in diverse topographic and climatic area in Pakistan - Muhammad Masood; Ghulam Nabi; Muhammad Babur; Aftab Hussain Azhar; Muhammad Kaleem Ullah (Journal of Mountain Science, 2021)

Diversity and recombination analysis of Cotton leaf curl Multan betasatellite associated with cotton leaf curl begomovirus disease complex - Muhammad Zubair; Saleem Ur Rahman; Ishtiaq Hassan; Azhar Hussain Shah; Imran Amin; Shahid Mansoor (Australasian Plant Pathology, 2021)

Lead contamination in shooting range soils and its phytoremediation in Pakistan: a greenhouse experiment - Amir Zeb Khan; Sardar Khan; Said Muhammad; Shams Ali Baig; Abdullah Khan; Muhammad Jamal Nasir; Madiha Azhar; Alia Naz (Arabian Journal of Geosciences, 2021)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Sedimentological attributes of the Middle Jurassic peloids-dominated carbonates of eastern Tethys, lesser Himalayas, Pakistan - Abdus Saboor; Muhammad Haneef; Muhammad Hanif; Muhammad Azhar Farooq Swati (Carbonates and Evaporites, 2020)

Predicting peak summer monsoon precipitation over Pakistan in ECMWF SEAS5 and North American Multimodel Ensemble - Muhammad Azhar Ehsan; Michael K. Tippett; Fred Kucharski; Mansour Almazroui; Muhammad Ismail (International Journal of Climatology, 2020)
The potential and actual forecast skill of peak summer monsoon precipitation (July–August [JA]) over the core summer monsoon region of Pakistan (CSMRP: 68°–76°E, 30°–36°N) is investigated. The predictions from the latest version of the European Centre for Medium‐Range Weather Forecast System5 (SEAS5) and the North American Multimodel Ensemble (NMME) initialized in the beginning of June, May, and April are utilized. The potential skill is estimated by signal‐to‐noise ratio and perfect model correlation. The forecast skill is evaluated using the temporal anomaly correlation as well as the ranked probability skill score for probabilistic forecasts. The SEAS5 generally captures the observed climatological mean and variability patterns of peak summer monsoon precipitation over the region, with some biases mainly located over the complex topography zones. Observed SST anomalies in the El Niño–Southern Oscillation (ENSO) region are negatively correlated with observed peak summer monsoon precipitation over the region. The ENSO–precipitation connection is weakly reproduced in SEAS5 at Lead‐1 and fades gradually with increasing lead time. The potentially predictable component (signal) is small compared to the unpredictable part (noise). Nonetheless, statistically significant potential skill is found over the CSMRP. However, the forecast skill of peak summer monsoon precipitation over the region is lower than the potential skill in SEAS5. A multimodel ensemble average of five models shows little benefit in predicting peak monsoon precipitation over Pakistan. Extended spatial averaging has some impact on the skill; however, temporal averaging has no effect on the skill of the summer monsoon precipitation in SEAS5. Together these results show limitations of the current seasonal prediction models and demonstrate their inadequate performance in predicting peak summer monsoon precipitation over Pakistan.

Evaluating the relationship between climate variability and agricultural crops under indeterminacy - Azhar Ali Janjua; Muhammad Aslam; Naheed Sultana (Theoretical and Applied Climatology, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

Assessment of Real Time, Multi-Satellite Precipitation Products under Diverse Climatic and Topographic Conditions - Muhammad Masood; Abdul Sattar Shakir; Aftab Hussain Azhar; Guhlam Nabi; Habib-u-Rehman (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Social and administrative issues related to the COVID-19 pandemic in Pakistan: better late than never - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Xuan Hinh Vo; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Application of geoelectrical resistivity method for the assessment of shallow aquifer quality in landfill areas - Nur Islami; Mitri Irianti; Fakhruddin Fakhruddin; Azhar Azhar; Muhammad Nor (Environmental Monitoring and Assessment, 2020)

Bioaccumulation of potentially toxic elements in spinach grown on contaminated soils amended with organic fertilizers and their subsequent human health risk - Zawar Hussain; Mehboob Alam; Muhammad Amjad Khan; Muhammad Asif; Muhammad Azhar Shah; Shehnaz Khan; Sardar Khan; Javed Nawab (Arabian Journal of Geosciences, 2020)

The impacts of COVID-19 measures on global environment and fertility rate: double coincidence - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Xuan Hinh Voo; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Air Quality, Atmosphere & Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Examining the impacts of future land use/land cover changes on climate in Punjab province, Pakistan: implications for environmental sustainability and economic growth - Abdus Samie; Azhar Abbas; Muhammad Masood Azeem; Sidra Hamid; Muhammad Amjed Iqbal; Shaikh Shamim Hasan; Xiangzheng Deng (Environmental Science and Pollution Research, 2020)

Biofloc-based co-culture systems of Nile tilapia (Oreochromis niloticus) and redclaw crayfish (Cherax quadricarinatus) with different carbon–nitrogen ratios - Muhammad H. Azhar; Suciyono Suciyono; Darmawan S. Budi; Mohammad F. Ulkhaq; Mai Anugrahwati; Julie Ekasari (Aquaculture International, 2020)

Genome-wide association study identifies various loci underlying agronomic and morphological traits in diversified potato panel - Muhammad Abu Bakar Zia; Ufuk Demirel; Muhammad Azhar Nadeem; Mehmet Emin Çaliskan (Physiology and Molecular Biology of Plants, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Potential predictability of boreal winter precipitation over central-southwest Asia in the North American multi-model ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui (Climate Dynamics, 2020)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Influence of biochar amendment and foliar application of iron oxide nanoparticles on growth, photosynthesis, and cadmium accumulation in rice biomass - Muhammad Rizwan; Shamaila Noureen; Shafaqat Ali; Sarwat Anwar; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Azhar Hussain (Journal of Soils and Sediments, 2019)

Time-dependent impairments in learning and memory in Streptozotocin-induced hyperglycemic rats - Ayaz Ahmed; Guirong Zeng; Dejiang Jiang; Haiying Lin; Mudassar Azhar; Ahsana Dar Farooq; Muhammad Iqbal Choudhary; Xinmin Liu; Qiong Wang (Metabolic Brain Disease, 2019)

Potential predictability of Arabian peninsula summer surface air temperature in the North American multimodel ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui; Muhammad Ismail; Michael K. Tippett (Climate Dynamics, 2019)

Vulnerability, well-being, and livelihood adaptation under changing environmental conditions: a case from mountainous region of Pakistan - Laila Shahzad; Arifa Tahir; Faiza Sharif; Waqas Ud Din Khan; Muhammad Ansar Farooq; Azhar Abbas; Zulfiqar Ahmad Saqib (Environmental Science and Pollution Research, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Genome-wide identification and expression analyses of WRKY transcription factor family members from chickpea (Cicer arietinum L.) reveal their role in abiotic stress-responses - Muhammad Waqas; Muhammad Tehseen Azhar; Iqrar Ahmad Rana; Farrukh Azeem; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Gyuhwa Chung; Rana Muhammad Atif (Genes & Genomics, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Bioremediation of tannery effluent by Cr- and salt-tolerant bacterial strains - Sobia Ashraf; Muhammad Naveed; Muhammad Afzal; Sana Ashraf; Khadeeja Rehman; Azhar Hussain; Zahir Ahmad Zahir (Environmental Monitoring and Assessment, 2018)

Influence of salinity and Fusarium oxysporum as the stress factors on morpho-physiological and yield attributes in onion - Amna Shoaib; Sidra Meraj; Nafisa; Kashif Ali Khan; Muhammad Azhar Javaid (Physiology and Molecular Biology of Plants, 2018)

Sustainable survival under climatic extremes: linking flood risk mitigation and coping with flood damages in rural Pakistan - Azhar Abbas; T. S. Amjath-Babu; Harald Kächele; Muhammad Usman; M. Amjed Iqbal; Muhammad Arshad; M. Adnan Shahid; Klaus Müller (Environmental Science and Pollution Research, 2018)

Anaerococcus jeddahensis sp. nov., a New Bacterial Species Isolated From Healthy Nomadic Bedouin Woman From Saudi Arabia - Niokhor Dione; Sara Bellali; Muhammad Yasir; Esam I. Azhar; Fehmida Bibi; Mamadou Beye; Nicholas Armstrong; Frédéric Cadoret; Asif A. Jiman-Fatani; Nayel Helmy; Jaishriram Rathored; Noémie Labas; et al. (Current Microbiology, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Silicon-mediated growth and yield improvement of sunflower (Helianthus annus L.) subjected to brackish water stress - Syed Azhar Hussain; Muhammad Ansar Farooq; Javaid Akhtar; Zulfiqar Ahmad Saqib (Acta Physiologiae Plantarum, 2018)

Changes in the nutritional composition of maize flour due to Tribolium castaneum infestation and application of carbon dioxide to manage this pest - Khalid Mehmood; Mureed Husain; Muhammad Aslam; Muhammad Shoaib Ahmedani; Azhar Mehmood Aulakh; Farid Asif Shaheen (Environmental Science and Pollution Research, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

Ag@MnxOy: an effective catalyst for photo-degradation of rhodamine B dye - Muhammad Saeed; Aziz Ahmad; Rajender Boddula; Inamuddin; Atta ul Haq; Aisha Azhar (Environmental Chemistry Letters, 2018)

In vitro growth inhibition and cytotoxicity of Euphorbia caducifolia against four human cancer cell lines and its phytochemical characterisation - Shaista Bano; Bina Shaheen Siddiqui; Ahsana Dar Farooq; Sabira Begum; Faheema Siddiqui; Muhammad Kashif; Mudassar Azhar (Natural Product Research, 2017)

Sensitivity of AGCM ‐simulated regional JJAS precipitation to different convective parameterization schemes - Muhammad Azhar Ehsan; Mansour Almazroui; Ahmed Yousef; O'Brien Enda; Michael K. Tippett; Fred Kucharski; Abdulrahman A. Alkhalaf (International Journal of Climatology, 2017)
This study examines the effects of convective parameterization schemes ( CPSs ) on the simulated June–September ( JJAS ) precipitation climatology, variability and predictability over southwestern Arabian Peninsula and northeast Africa during 1981–2014 within an atmospheric global climate model framework. The three CPSs used are: the simplified Arakawa–Schubert ( SAS ) scheme; the SAS scheme with Tokioka modification ( STOK ) and the Emanuel ( EMAN ) scheme coupled with a probability distribution function‐based cloud parameterization scheme. SAS and STOK overestimate JJAS total precipitation over the selected domain compared to observations, while EMAN underestimates. EMAN provides the most realistic distribution of precipitation and spatial distribution of convective precipitation despite the tendency for underestimating the total precipitation. The principal patterns of precipitation variability (as measured by the leading empirical orthogonal functions) in EMAN and STOK are clearly related to the observed pattern, while the maximum variability in SAS occurs in a completely different location. The El Niño Southern Oscillation‐related JJAS precipitation teleconnection simulated by the SAS scheme is very weak as compared to observations and other two CPSs . The signal‐to‐noise ratio estimated by SAS and STOK is very low as compared to EMAN . Correlation analysis shows that EMAN performs better than the other two CPSs . Low (high) outgoing longwave radiation ( OLR ) values are indicative of enhanced (suppressed) convection and hence more (less) cloud coverage. The root mean square error estimated for OLR in EMAN is lower than that of the other two CPSs . The vertical structure of specific humidity and temperature shows less error in EMAN than that of the other two CPSs , which could be a reason for better predictability over the region of interest.

Comparison of rhizosphere properties as affected by different Bt- and non-Bt-cotton (Gossypium hirsutum L.) genotypes and fertilization - Maqshoof Ahamd; Waleed Mumtaz Abbasi; Moazzam Jamil; Muhammad Iqbal; Azhar Hussain; Muhammad Fakhar-u-Zaman Akhtar; Farheen Nazli (Environmental Monitoring and Assessment, 2017)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Climate variability and yield risk in South Asia’s rice–wheat systems: emerging evidence from Pakistan - Muhammad Arshad; T. S. Amjath-Babu; Timothy J. Krupnik; Sreejith Aravindakshan; Azhar Abbas; Harald Kächele; Klaus Müller (Paddy and Water Environment, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Effects of in situ habitat quality and landscape characteristics in the oil palm agricultural matrix on tropical understory birds, fruit bats and butterflies - Badrul Azhar; Chong Leong Puan; Najjib Aziz; Muhammad Sainuddin; Nurfatin Adila; Sohaimi Samsuddin; Siti Asmah; Muhamad Syafiq; Syafiq A. Razak; Ahmad Hafizuddin; Ainil Hawa; Syari Jamian (Biodiversity and Conservation, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Fahad Irfan Siddiqui; Dur Muhammad Pathan; Syed Baharom Azhar Bin Syed Osman; Munawar Ali Pinjaro; Safiullah Memon (Arabian Journal of Geosciences, 2015)

Geochemical assessment of metal pollution and ecotoxicology in sediment cores along Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Nisar Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2015)

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Faiza Sajjad; Muhammad Azhar Khan; Muhammad Zahir Khan (Environmental Science and Pollution Research, 2014)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Metal pollution and ecological risk assessment in marine sediments of Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2013)

Letter to the Editor: Cotton leaf curl Multan betasatellite strains cloned from Gossypium barbadense further supports selection due to host resistance - Muhammad Tehseen Azhar; Sohail Akhtar; Shahid Mansoor (Virus Genes, 2012)

Dracorhodin perchlorate inhibits PI3K/Akt and NF-κB activation, up-regulates the expression of p53, and enhances apoptosis - Azhar Rasul; Chuan Ding; Xiaomeng Li; Muhammad Khan; Fei Yi; Muhammad Ali; Tonghui Ma (Apoptosis, 2012)

Determination of radioactive elements and heavy metals in sediments and soil from domestic water sources in northern peninsular Malaysia - Bashir G. Muhammad; Mohammad Suhaimi Jaafar; Azhar Abdul Rahman; Farouk Abdulrasheed Ingawa (Environmental Monitoring and Assessment, 2012)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Characterization of resistance gene analogs from Gossypium arboreum and their evolutionary relationships with homologs from tetraploid cottons - Muhammad Tehseen Azhar; Imran Amin; Aftab Bashir; Shahid Mansoor (Euphytica, 2011)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)

Both malvaceous and non-malvaceous betasatellites are associated with two wild cotton species grown under field conditions in Pakistan - Muhammad Tehseen Azhar; Imran Amin; Zahid Iqbal Anjum; Muhammad Arshad; Rob W. Briddon; Shahid Mansoor (Virus Genes, 2010)

Ultrastructural alterations produced in cockerels after mercuric chloride toxicity and subsequent interaction with an organophosphate insecticide - Muhammad Azhar Chishti; Tadeusz Rotkiewicz (Archives of Environmental Contamination and Toxicology, 1992)